Reviewing feminist macroeconomics for the XXI century - Izaskun Zuazu-Bermejo (University of Duisburg-Essen, Institute for Socio-Economics (ifso), 2024)
Feminist macroeconomics draws on the notion that the gender system is both cause and consequence of macroeconomic structures, outcomes, and policies. In contrast, mainstream and heterodox macroeconomics have done little to integrate gender as an analytical tool in macromodelling. This paper defines the subfield of feminist macroeconomics, explores its origins, and provides a systematic review of its literature. Drawing on Seguino (2013), the paper divides the subfield in three main strands: i) feminist growth theory and gender dimensions of macrolevel policies, ii) macro-modelling and theoretical foundations of the care economy, and iii) social infrastructure and intra-household allocation. The paper discusses potential ways to expand the foci of feminist macroeconomic research, while considers challenges to the subfield, such as methodological issues regarding male-biased metrics and limited data availability, and the tensions with mainstream approaches to gender and the macroeconomy. Finally, the paper contextualizes the subfield in a post-pandemic era.
Keywords: E0; E12; B54; 330; feminist macroeconomics; feminist growth theory; care economy; COVID-19 pandemic; economic methodology